Profile of Polya's Problem-Solving Abilities Model Among Senior High School Students: Lesson From Stoichiometric Class - Herunata Herunata; Nur Kholilah (Universitas Negeri Malang, 2021)
Based on several studies, it is known that there are students' difficulties in applying problem-solving as a problem-solving method, especially in stoichiometric material. Because solving stoichiometric' problems requires not only algorithmic skills but also a good understanding of chemical concepts. This study uses subjective test questions to determine the steps or methods students use to solve problem-solving test questions. The results showed that the students' problem-solving ability in the upper group was very high, the middle group was quite high. In contrast, the lower group was classified as low with mastery of Polya steps, respectively 85%, 68%, and 36%. There is a significant correlation between students' mastery of problem-solving steps. The correlation of mastery of problem-solving steps for students in the upper group was 0.786 (high), the middle group was 0.883 (very high), and the lower group had a correlation score of 0.803 (very high).REFERENCESAmalia, F.R. 2015. Identifikasi Kesulitan Siswa Kelas XI MIA SMA Negeri 1 Kauman Tulungagung dalam Menyelesaikan Soal-soal Stoikiometri Menggunakan Analisis Langkah Penyelesaian Soal. Skripsi tidak diterbitkan. Malang: FMIPA Universitas Negeri Malang.Bodner, George M. & Herron, J. Dudley. 2002. Problem Solving in Chemistry. Chemical Education: Towards Research-based Practice Kluwer, 235–266Bodner, George M. & Domin, Daniels. 2000. Mental Models: The Role of Representations in Problem Solving in Chemistry. University Chemistry Education. 4: 24-30.Chang, Raymond. 2005. Kimia Dasar: Konsep-Konsep Inti Jilid 1/ Edisi ketiga. Bandung: ErlanggaChiu, M.H. 2001. Algorithmic Problem Solving and Conceptual Understanding of Chemistry by Student at a Local High School in Taiwan. Journal of Chemical Education International, 11(1): 20-38.Chiu, M.H. 2005. A National Survey of Students' Conceptions in Chemistry in Taiwan. Chemical Education International, 6 (1): 1-8.Effendy. 2006. A-Level Chemistry for Senior High Students Volume 2A. Malang: Bayumedia Publishing.Gabel, Dorothy L., Sherwood, Robert D., & Enochs, Larry. 1984. Problem-Solving Skills of High School Chemistry Students. Journal of Research in Science Teaching. 21 (2): 221-233Hiebert, J. 1985. Conceptual and Procedural Knowledge: The Case of Mathematics. London: Lawrence Enibaum Associates.Nurjannah, Fitria. 2014. Analisis Langkah-Langkah Dalam Menyelesaikan Masalah Perhitungsn Pada Materi Stokiometri Siswa Kelas X SMA Negeri 1 Situbondo. Skripsi tidak diterbitkan. Malang: FMIPA Universitas Negeri Malang.Polya, G. 1957. How to solve it: a New Aspect of mathematical method. Princeton, USA: Princeton University PressSilberberg, Martin S. 2009. Chemistry The Molecular Nature of Matter Fifth Edition. New York: Mcgraw-hillSugiyono, 2015. Memahami Penelitian Kualitatif. Bandung: Alfabeta.Zidny, Robby, Sopandi, Wahyu, Kusrijadi, Ali. 2013. Analisis Pemahaman Konsep Siswa SMA Kelas X pada Materi Persamaan Kimia dan Stoikiometri melalui Penggunaan Diagram Submikroskopik serta Hubungannya dengan Kemampuan Pemecaham Masalah. Jurnal Riset dan Praktik Pendidikan Kimia. 1(1)